Additional measurements of volatile organic compounds by PTR-ToF-MS at Cataract Scout Park, Australia, taken during the COALA-2020 campaign - Asher P Mouat; Jennifer Kaiser; Clare Paton-Walsh; Jhonathan Ramirez-Gamboa; Travis A Naylor; Jack B Simmons (PANGAEA, 2021)
Measurements of volatile organic compounds (VOCs) were collected using an Ionicon 4000 Proton Transfer Reaction Time of Flight Mass Spectrometer (PTR-ToF-MS). Measurements were taken at Cataract Scout Park, Appin, N.S.W. (34°14 extquotesingle42.29S 150°49 extquotesingle24.97E) from an inlet 10 m above ground level as part of the Characterizing Organics and Aerosol Loading over Australia (COALA-2020) campaign. The campaign ran from mid-January to mid-March, 2020, with the instrument running from early February. Data presented here corresponds to data used in paper by Mouat et al. (2021a) which spans from 2-6 Feb. 2020. These species are in addition to directly calibrated species archived by Mouat et al. (2021b) in a seperate PANGAEA record. Sample air was drawn down a 20 m PTFE inlet line with a bypass pump (flow rate 1.5 – 3 Lmin-1). Concentrations for compounds presented in this dataset were calculated using methodology proposed in Sekimoto et al. (2017).